Using NT-proBNP to Detect Chronic Heart Failure in Elderly Patients with Chronic Obstructive Pulmonary Disease. (9th June 2013) - Kaszuba, Elzbieta; Wagner, Bartlomiej; Odeberg, Håkan; Halling, Anders
Abstract : Objective . To detect chronic heart failure in elderly patients with a registered diagnosis of chronic obstructive pulmonary disease (COPD) treated in Swedish primary health care using natriuretic peptide NT-proBNP. Design . A cross-sectional study. Setting . Two primary health care centres in southeastern Sweden each with about 9000 listed patients. Subjects . Patients aged 65 years and older with a registered diagnosis of COPD. Main Outcome Measures . Percentage of patients with elevated NT-proBNP, percentage of patients with abnormal left ventricular function assessed by echocardiography, and association between elevated NT-proBNP and symptoms, signs, and electrocardiography. Results . Using NT-proBNP threshold of 1200 pg/mL, we could detect and confirm chronic heart failure in 5.6% of the study population with concurrent COPD. An elevated level of NT-proBNP was only associated with nocturia and abnormal electrocardiography. Conclusions . We found considerably fewer cases of heart failure in patients with COPD than could be expected from the results of previous studies. Our study shows the need for developing improved strategies to enhance the validity of a suspected heart failure diagnosis in patients with COPD.